متطلبات استخدام التعليم الإلكتروني في تدريس العلوم في المرحلة الثانوية من وجهة نظر المدرسين ((دراسة ميدانية في المدارس الثانوية العامة في محافظة دمشق)) - الياس اسما; جبلاوي رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى تحديد متطلبات استخدام التعليم الإلكتروني في تدريس العلوم الطبيعية في المرحلة الثانوية العامة الواجب توافرها في (الطالب، المنهج، المدرس، والبيئة التعليمية). وتعرّف الفروق بين إجابات المدرسين تبعاً لمتغيرات البحث: (سنوات الخبرة، الدورات التدريبية، التخصص في العلوم، المؤهل التربوي). واستخدمت الباحثة الاستبانة كأداة للدراسة. وشملت عينة البحث (200) مدرساً ومدرسة من (مدرسي العلوم) في مدارس محافظة دمشق. وتوصل البحث إلى نتائج أهمها: تراوح متوسطات البنود المتعلقة بتدرج المناهج التعليمية وتنظيمها وتطويرها من قبل المتخصصين في المناهج بين (4,93 و 4,28)، كما تراوحت متوسطات إجابات المدرسين لاستخدام التعليم الإلكتروني في تعليم العلوم الطبيعية بين (4,98 و 3,74)، أما متطلبات البيئة التعليمية فقد تراوحت متوسطاتها الحسابية بين (4,92 و 3,55) وركزت المطالب على توفير حجرات الدراسة والقاعات التدريبية لاستخدام التعليم الإلكتروني. وبيّنت الدراسة وجود فروق دالة إحصائياً تعزى لمتغير المؤهل العلمي لصالح حملة دبلوم التأهيل التربوي, وأظهرت وجود فروق تعزى لمتغير سنوات الخبرة لصالح الأفراد الذين يمتلكون خبرة أقل من خمس سنوات، ويتوجب عليهم الأخذ بمتطلبات استخدام التعليم الإلكتروني، كما بينت النتائج وجود فروق دالة إحصائياً لصالح المدرسين الذين خضعوا لدورات تدريبية, ووجود فروق دالة إحصائياً في متطلبات استخدام التعليم الإلكتروني تعزى لمتغير التخصص لصالح حملة الإجازة في تخصص علم الأحياء, وتوصل البحث إلى عدد من المقترحات، أهمها: الاستفادة من المتطلبات التي حددتها الدراسة في بناء مناهج العلوم الطبيعية بطريقة إلكترونية, ومراعاة وزارة التربية في عملية قبول المدرسين هذه المتطلبات, ومراعاة البيئة التعليمية التي ينفذ فيها التعليم الإلكتروني الإمكانات المادية والبشرية لتنفيذه, وإجراء دورات تدريبية للمدرسين على برامج التعليم الإلكتروني. The aim of this research is to identify the requirements of using e-learning in teaching natural sciences at the secondary level. These requirements are supposed to be found in the student, the teacher, the curriculum, and the learning environment. The differences between the answers of teachers are defined depending on the search variables: (years of experience, training courses, specialization in science, educational qualification). The researcher used a questionnaire as a tool. The research sample included (200) teachers natural sciences in schools in the province of Damascus. The research yielded several results, the most important of which are: - The averages the teachers’ answers on the items related to the progression, organization and development of curricula by specialists ranged between(4. 93) and (4. 28). - The averages the teachers’ answers on the items related to the use of e-learning in the teaching of natural sciences ranged between (3.74) and(4.98). - The averages the teachers’ answers on the items related to the requirements of educational environment ranged between (3.55) and (4.92). The teachers mainly demanded the provision of classrooms and training halls for using e-learning. The study’s results also showed statistically significant differences regarding the educational qualification variable, in favor of those who have got an educational qualification diploma. They showed statistically significant differences regarding the years of experience variable, in favor of those who have got less than five years of experience and ought to use the e-learning. There are also statistically significant differences regarding the training courses variable, in favor of those who have taken training courses, as well statistically significant differences regarding the variable of specialization, in favor of those who have got a BA in biology. The research recommends benefitting from the requirements identified by the research in developing natural sciences curricula electronically. It also recommends that the Ministry of Education takes these requirements into consideration when it recruits teachers, and puts more effort in executing the e-learning educational environment through material and human resources. Finally, training courses for teachers on e-learning programs should be done.